Challenges in Business Analytics Implementation: A Comprehensive Review Using TOE Framework - Daniel Peterson Silaban (Universitas Pelita Harapan, 2022)
Business analytics are changing how firms treat data. Using analytics, firms possess the capability to capture greater insights and predict the future, hence better decision-making process. However, the implementation of analytics in business has to be carried within the complexity of organization, technology, and environment. Given the complexity, this study aims to identify the challenge faced by firms across industries. The TOE framework is utilized to construct a more comprehensive framework of the challenges. Past studies related to implementation of business analytics are gathered and processed using literature review method. This study helps Asian firms to be more anticipative by providing a holistic and clearer view of challenges in adopting business analytics.